Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Untuk Penggunaan Uang Elektronik Dalam Melakukan Transaksi Pembayaran Online Di Desa Tanjung Tirto Kecamatan Way Bungur Lampung Timur - Rahmad, Saputra Dian; Imantoro, Jati (Jurnal Manajemen DIVERSIFIKASI, 2022)
Electronic money is a means of payment that makes it easy for users to make transactions safely, quickly and efficiently. However, in the level of understanding of the special residents of TanjungTirto Village, there are still many who do not understand the functions and conveniences. So, the researchers conducted an intensive study of the public about the importance of using electronic money. The purpose of this study is to find out (1) the role of the level of understanding of interest in the use of electronic money. (2) The role of expediency on interest in using electronic money. (3) whether the level of understanding and usefulness simultaneously has a role in the interest in using electronic money in the people of TanjungTirto Village, Way-Bungur District, East Lampung. This research is a quantitative research.The population of which is the people of TanjungTirto Village, totaling 378 people. While the data collection using a questionnaire through google form, while the data analysis technique in this research uses multiple linear regression through partial t-test and simultaneous f-test and the coefficient of determination (R2). The results showed that (1) in the level of understanding using electronic money in TanjungTirto Village, Way-Bungur District, East Lampung, they did not fully understand because of one's ability to understand that electronic money is an alternative means of payment which is then interpreted and understood by each test result. The t-value is 4.241 and the t-table value is 1.975. (2) for the benefits of using electronic money, many people already known about the benefits and functions of the level of confidence where someone believes in the benefits of electronic money with the value of the t-test results obtained by the t-count value of 3.955 and the t-table value of 1.975. The conclusion is that simultaneously the two independent variables have a good role in the interest in using electronic money in TanjungTirto Village, Way-Bungur District, East Lampung, and the coefficient of determination of 0.251 or 25.1% is influenced by other variables. Suggestions for the people of TanjungTirto Village for their level of understanding of using electronic money in obtaining information from advertisements on television so that they study and observe so that they can use it properly.